Complete Dose of Hepatitis B Vaccination Among Children in Indonesia and Factors Associated: A Community-Based Study - Machmud, Putri Bungsu; Gayatri, Dwi; Astutik, Erni (UI Scholars Hub, 2024)
Hepatitis B vaccination is widely recognized as the most effective way to prevent hepatitis B infection, yet the rate of complete vaccination among Indonesian children remains low. This study aimed to evaluate the extent of hepatitis B vaccination coverage among children and identify potential associated factors in Indonesia. A community-based cross-sectional study was conducted. The study involved 7,860 Indonesian mothers of children aged 12-59 months, providing data on their children's hepatitis B vaccination status and other relevant factors from the 2017 Indonesian Demographic Health Survey. Overall, the rate of complete hepatitis B vaccination among children was relatively high (89.8%). Several factors were found to be associated with complete hepatitis B vaccination among children: living in Java, the Lesser Sunda Islands, Kalimantan, and Sulawesi compared to Sumatra; having an older mother; having parents with secondary or higher education compared to no education; having an employed mother; belonging to middle or high economic status compared to low economic status; having mothers using media irregularly or regularly, as opposed to never using media; having health insurance; and having a larger family size. These findings highlight the need for further interventions to optimize childhood hepatic vaccination coverage, which health policymakers should support.